2015
DOI: 10.1093/abbs/gmv024
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125b-5p inhibits proliferation and promotes adipogenic differentiation in 3T3-L1 preadipocytes

Abstract: Previous evidence has indicated that the microRNA-125b (miR-125b) family plays important roles in the regulation of cancer cell growth, development, differentiation, and apoptosis. However, whether they contribute to the process of adipocyte differentiation remains unclear. In the present study, we revealed that the expression level of miR-125b-5p, a member of miR-125b family, was dramatically up-regulated during differentiation of 3T3-L1 preadipocyte into mature adipocyte. Supplement of miR-125b-5p into 3T3-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…Furthermore, our results revealed that knockdown of Smad4 gene or overexpression of miR-144-3p inhibited the proliferation of MSCs (Fig. 6), which is consistent with Dan et al who have reported that miR-125b-5p inhibits proliferation in 3T3-L1 preadipocytes by targeting Smad4 [35]. Additionally, we found that Smad4 knockdown blocks the effects of miR-144-3p ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our results revealed that knockdown of Smad4 gene or overexpression of miR-144-3p inhibited the proliferation of MSCs (Fig. 6), which is consistent with Dan et al who have reported that miR-125b-5p inhibits proliferation in 3T3-L1 preadipocytes by targeting Smad4 [35]. Additionally, we found that Smad4 knockdown blocks the effects of miR-144-3p ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Although the importance of Smad4 in osteogenic differentiation has been proposed in certain reports, including a study describing the reduction of bone mineral density, bone volume, and osteoblast numbers in osteoblast‐specific Smad4 conditional KO mice and one on the role of miR‐144‐3p‐targeting Smad4 in osteogenic differentiation , our findings extend our knowledge about the molecular mechanism of Smad4 as a positive factor in the osteogenic differentiation of MSCs. In contrast, a possible role of Smad4 in adipogenic differentiation was predicted by a previous report that miR‐125b‐5p could potentially target Smad4 in preadipocyte 3T3‐L1 cells , but this report did not demonstrate the exact mechanism of Smad4 as a negative factor in adipogenic differentiation. Therefore, our results provide a clue about the inverse reciprocal regulation between the osteogenesis and adipogenesis of MSCs.…”
Section: Discussioncontrasting
confidence: 83%
“…In order to investigate if this is also true for human adipogenesis, we overexpressed miR125b-5p in preadipocytes and analyzed the global mRNA expression via Illumina BeadChip Microarray. However, Smad4 was not downregulated, indicating that it is no direct target of miR125b-5p during human adipogenesis 38 . Nonetheless, we identified CCAAT/enhancer-binding protein β (CEBPB), CCAAT/enhancer-binding protein delta (CEBPD) , and early B-cell factor 1 EBF1 as significantly downregulated (data not shown) after miR125b-5p overexpression.…”
Section: Discussionmentioning
confidence: 87%